Knowledge, Attitude and Practice (KAP) Regarding Pediatric Immunization Among Mothers in Rural Maharashtra: A Cross-Sectional Study. - Bobade, Ravindra (Journal of Neonatal Surgery, 2016)
Background: Childhood immunization is a key public health intervention for reducing morbidity and mortality due to vaccine-preventable diseases. Mothers play an important role in ensuring timely and complete immunization of children, especially in rural communities. Objective: To assess the knowledge, attitude and practice regarding pediatric immunization among mothers in rural Maharashtra and to identify factors associated with complete immunization. Methods: A cross-sectional study was conducted from July 2015 to Dec 2015 among 300 mothers aged 18–40 years having at least one child under five years of age in 10 randomly selected villages of Aurangabad district, Maharashtra. Data were collected using a pre-tested semi-structured questionnaire covering socio-demographic profile, knowledge, attitude and immunization practice. Immunization status of the youngest child was assessed and verified by immunization card where available. Data were analyzed using descriptive statistics and Chi-square test. Results: The mean age of mothers was 28.4 ± 5.2 years. Overall, 62% of mothers had good knowledge and 78% had a positive attitude towards immunization. Although 85% knew that vaccines prevent diseases, only 42% were aware of the complete immunization schedule. Complete immunization was observed in 55% of children, while 32% were partially immunized and 13% were unimmunized or minimally immunized. Major reasons for default were illness of the child, lack of time/transport, forgetting the date and fear of side effects. Maternal education, socio-economic status and regular contact with ASHAs/ANMs were significantly associated with better KAP and complete immunization. Conclusion: Despite favourable attitude, gaps persisted in detailed knowledge and complete immunization practice. Strengthening maternal counselling, reminder systems and frontline worker follow-up may improve immunization coverage in rural Maharashtra...